Long-term atrial arrhythmias incidence after heart transplantation. (15th July 2020) - Anselmino, Matteo; Matta, Mario; Saglietto, Andrea; Gallo, Chiara; Gaita, Fiorenzo; Marchetto, Giovanni; Rinaldi, Mauro; De Ferrari, Gaetano Maria; Boffini, Massimo
Abstract: Objectives: Atrial arrhythmias after heart transplantation have rarely been investigated. The aim of this study is to assess incidence, type and predictors of atrial arrhythmias during a long-term follow-up in a large population of heart-transplanted patients. Methods: Consecutive patients undergone to heart transplantation at our Centre from 1990 to 2017 were enrolled. All documented atrial arrhythmias were systematically reviewed during a long-term follow-up after heart transplantation. Atrial fibrillation (AF), atrial flutter and tachycardias were defined according to current guidelines. Results: Overall, 364 patients were included and followed for 120 ± 70 months. During the follow-up period 108 (29.7%) patients died and 3 (0.8%) underwent re-transplantation. Sinus rhythm was present in 355 (97.5%) patients. Nine patients had persistent atrial arrhythmias: 8 (2.2%) presented atypical flutter and one (0.3%) patient AF. Paroxysmal sustained arrhythmias were detected in 42 (11.5%) patients, always atrial flutters. At univariate analysis several echocardiographic (left ventricular end-diastolic diameter, TEI index, mitral and tricuspid regurgitation grade) hemodynamic (systolic and diastolic pulmonary pressure, capillary wedge pressure) and clinical (dyslipidaemia, weight, pacemaker implantation) parameters related to higher incidence of atrial arrhythmias. Conclusion: Persistent atrial arrhythmias, and most of all AF, are rare among heart transplantation carriers, despite substantial comorbidities resulting in significant mortality. It can be speculated that the lesion set provided by the surgical technique, a complete and transmural electrical isolation of the posterior left atrium wall, represents an effective lesion set to prevent persistent AF. Highlights: Heart transplantation creates electrical barriers, similar to surgical AF ablation. Heart transplantation carriers may experience non-AF paroxysmal atrial arrhythmias. Persistent AF in heart transplantation carriers is extremely rare. Complete electrical left atrial posterior wall isolation prevents persistent AF.